Zeatin ribonucleosides in the transfer ribonucleic acid of Rhizobium leguminosarum, Agrobacterium tumefaciens, Corynebacterium fascians, and Erwinia amylovora. - Cherayil, J D (1977)
Until recently, the presence in transfer ribonucleic acid (tRNA) of the hydroxylated cytokinin ribosylzeatin [N6-(4-hydroxy-3-methylbut-2-enyl)adenosine]was thought to be unique to higher plants. This extension of work from several laboratories indicates the presence of 2-methylthioribosylzeatin in the tRNA of the plant-associated bacteria Rhizobium leguminosarum, Agrobacterium tumefaciens, and Corynebacterium fascians, but not in that of Erwinia amylovora. This cytokinin has the cis configuration, as is normally found in the tRNA's of plants. The tRNA thionucleotide patterns in these bacteria are different from those of Escherichia coli, Bacillus subtilis, and Salmonella typhimurium, which contain the unhydroxylated analogs of ribosylzeatin or 2-methylthioribosylzeatin.